Ectopic bone formation associated with mesenchymal stem cells in a resorbable calcium deficient hydroxyapatite carrier - Kasten, Philip; Vogel, Julia; Luginbühl, Reto; Niemeyer, Philip; Tonak, Marcus; Lorenz, Helga; Helbig, Lars; Weiss, Stefan; Fellenberg, Jörg; Leo, Albrecht; Simank, Hans-Georg; Richter, Wiltrud (Biomaterials, 2005)
Bone substitute materials can induce bone formation in combination with mesenchymal stem cells (MSC). The aim of the current study was to examine ectopic in vivo bone formation with and without MSC on a new resorbable ceramic, called calcium deficient hydroxyapatite (CDHA). Ceramic blocks characterized by a large surface (48 m2/g) were compared with beta-tricalcium phosphate (beta-TCP), hydroxyapatite (HA) ceramics (both ca. 0.5 m2/g surface) and demineralized bone matrix (DBM). Before implantation in the back of SCID mice carriers were freshly loaded with 2x10(5) expanded human MSC or loaded with cells and kept under osteogenic conditions for two weeks in vitro. Culture conditions were kept free of xenogenic supplements. Deposits of osteoid at the margins of ceramic pores occurred independent of osteogenic pre-induction, contained human cells, and appeared in 416 MSC/CDHA composites compared to 216 MSC/beta-TCP composites. ALP activity was significantly higher in samples with MSC versus empty controls (p<0.001). Furthermore, ALP was significantly (p<0.05) higher for all ceramics when compared to the DBM matrix. Compared to previous studies, overall bone formation appeared to be reduced possibly due to the strict human protocol. Ectopic bone formation in the novel biomaterial CDHA varied considerably with the cell pool and was at least equal to beta-TCP blocks.
Gesehen am 30.06.2021